2022
DOI: 10.1016/j.psychres.2022.114391
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the LGBTQ+ community: Comparisons between cisgender, heterosexual people, cisgender sexual minority people, and gender minority people

Abstract: There is a dearth of public health data and research focusing on lesbian, gay, bisexual, transgender, queer, and other sexual and gender minority (LGBTQ+) populations during the coronavirus (“COVID”) pandemic. This study evaluated how COVID has impacted health, social, and occupational areas of functioning of the LGBTQ+ community. A community survey was distributed via email by local LGBTQ+ community organizations between September and December 2020. Participants (cisgender, heterosexual people, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 23 publications
3
19
0
1
Order By: Relevance
“…LGBTQ persons have a greater incidence asthma, cancer, diabetes, heart disease, substance use, and mental health symptoms—all of which are associated with minority stressors (e.g., discrimination, stigma) and predispose them to COVID-19 morbidity and mortality [ 4 , 8 , 9 , 10 , 11 ]. Furthermore, it has been reported in studies conducted in the US that LGBTQ adults were more likely to experience worsening physical and mental health compared to non-LGBTQ adults during the pandemic [ 6 , 8 , 12 ]. For instance, a study utilizing a national sample of US adults found loneliness, stress, psychological distress, and quality of life were worse among sexual minority individuals compared with non-sexual minority persons [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LGBTQ persons have a greater incidence asthma, cancer, diabetes, heart disease, substance use, and mental health symptoms—all of which are associated with minority stressors (e.g., discrimination, stigma) and predispose them to COVID-19 morbidity and mortality [ 4 , 8 , 9 , 10 , 11 ]. Furthermore, it has been reported in studies conducted in the US that LGBTQ adults were more likely to experience worsening physical and mental health compared to non-LGBTQ adults during the pandemic [ 6 , 8 , 12 ]. For instance, a study utilizing a national sample of US adults found loneliness, stress, psychological distress, and quality of life were worse among sexual minority individuals compared with non-sexual minority persons [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the pandemic, LGBTQ communities reported poorer healthcare access and quality (e.g., lack of insurance, financial constraints, medical mistrust due to discrimination), greater discrimination and stigma, and higher rates of poverty, unemployment, incarceration, and housing instability compared to non-LGBTQ people [ 9 , 13 , 14 ]. During the pandemic, LGBTQ adults have experienced greater job loss, financial instability, lack of basic needs, social isolation, and barriers to healthcare access [ 6 , 12 , 15 ]. LGBTQ individuals with intersectional identities, such as those who are also part of a racial/ethnic minority group, are at even greater risk [ 4 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This phase of life is consonant with the beginning of expressions of violence and aggression in their lives 3 , 41 - 42 . Not responding to the wishes and norms of the families is the first major obstacle experienced by these people 43 . For these reasons, suicidal behavior becomes common in the trans community, especially during youth, associated with the vexatious and violent situations to which they are exposed, causing melancholy, egodystonia, and deep sadness 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The imposed social distancing might have had an impact not only on psychological distress, but also on a quality of life. The population most at risk for this adverse impact were people from sexual and gender minorities [ 11 , 12 , 13 , 14 ]. Moreover, a relatively higher prevalence of psychological, physical, and sexual violence against women was noted [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%